Oxidative damage and antioxidant behaviour of ascorbate and glutathione in two onion genotypes differing in salt sensitivity (Bioagro, 2020)
Salinity is a limiting factor on the productivity of the onion, because this species is sensitive to salts. In this study, the effect of salinity on oxidative damage and the antioxidant behavior of ascorbate and glutathione, was evaluated in two genotypes of onion with different response to salts, in order to determinate if the antioxidant protection is related to their differential sensitivity to salts. Plants 40 days old of the genotypes ‘Granex 429’ and ‘Texas 502’, with low and high sensitivity to salt stress respectively, were stressed by a mixture of salts (CE 6 dS·m-1) for 20 days, maintaining a control group; after the end of the period, it was determined: degree of lipid peroxidation (DLP) and content of ascorbate and glutathione in roots and leaf. The salinity affected the DPL in leaves being that effect higher in ‘Texas 502’ than in ‘Granex 429’ while in roots this variable was not altered. The content of ascorbate in roots and leaves decreased with salinity in ‘Texas 502’ while in ‘Granex 429’ it not changed in roots, but in the leaf there was a significant increase in its concentration and redox state. With salinization the root content of glutathione was increased and the opposite occurred in the leaf of both genotypes. The results suggested that the lower sensitivity to salts in ‘Granex 429’ is associated with a better capacity of antioxidant protection of the foliar tissue, accomplished by an increase in the antioxidant activity of ascorbate.
Keywords: Allium cepa; ascorbate; glutathione; lipid peroxidation; onion; salinity stress